The impact of COVID-19 lockdowns on Norwegian athletes` training habits and their use of digital technology for training and competition purposes - Tjønndal, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
This article examines how strict nation-wide regulations and lockdowns affected athletes`training habits in Norway and, more specifically, their use of digital technology for sports training and competition purposes. This is analyzed using quantitative survey data from 953 Norwegian athletes collected during a lockdown in the spring of 2020. The results show that the athletes` use of digital technology for online training increased significantly during the lockdown. Logistic regression analyses indicate that there are age and gender differences in athletes` participation in online training and virtual sports competitions. Female athletes are more likely to participate in online training than male athletes, while male athletes are more likely to participate in virtual sports competitions than female athletes. Older athletes are more likely to participate in virtual competitions than younger athletes. Athletes living in urban areas are more likely to participate in digital training than those living in rural areas.